Impact of Different Carbohydrates on High Frequency Plant Regeneration from Axillary Buds of Mentha piperita (L.) – An Important Multipurpose Medicinal Plant - C.V. Naidu2*, P. Sujana1 and (Journal of Phytology, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-bidi-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">Mints are a group of plants belonging to family lamiaceae, which yield essential oils on distillation. Mentha piperita is a native of the Mediterranean region and has naturalized in Europe, Asia, North America and Australia. The plant is a perennial, glabrous herb with strong pepper-like pungent odour and hence the specific name Ã¢â‚¬Å“piperitaÃ¢â‚¬Â. Peppermint generally grows in shade and moist areas with a good water supply. The ideal way of planting this mint is in part-sun to shade areas, well drained soils with good water Ã¢â‚¬â€œ holding capacity are better suited for mint cultivation as it avoids frequent irrigation during summer andÃ‚Â  problems in rainy seasons. Mint does not tolerate water stagnation. Its oil is one of the most popular widely used essential oil in food products, cosmetics, pharmaceuticals, dental preparations, mouthwashes, soaps and alcoholic liquors. The influence of different sugars (sucrose, maltose, glucose, and fructose) and plant growth regulator BAP 2.0 mg/l and MS media were investigated for the development of multiple shoots from axillary bud or nodal explants of Mentha piperita. Among the different sugars tested, 4mg/ml fructose was the best for plant regeneration. Maximum number of shoots (27.6) was induced on the medium containing 4mg/ml fructose. Observations of the shoot cultures developed on media containing one of these carbohydrates indicated that fructose was the preferential carbon source for the proliferation of multiple shoots. In vitro shoots were then excised from the shoot clumps and transferred to rooting medium containing indole butyric acid (IBA - 1.5 mg/L). These shoots when removed from the culture tubes and transferred into sterile soil in green house, most of the plantlets survived (98%) and they were suitable for field planting after 1 month.